Multi-objective optimal scheduling of laminar cooling water supply system for hot rolling mills driven by digital twin for energy-saving. (February 2023) - Wang, Fenjia; Song, Yong; Liu, Chao; He, Anrui; Qiang, Yi
Abstract: As a result of the complex structure of laminar cooling water supply systems, both facets of strict process requirements and various intermittent running conditions could cause challenges of energy-saving and equipment upkeep. Given the energy wastage issue of the laminar cooling system of hot rolling, this paper develops an optimal scheduling system according to digital twin using Online Sequential Extreme Learning Machine (OS-ELM) and multi-objective evolutionary optimization using Improved Sparrow Search Algorithm (ISSA). The optimal scheduling system according to digital twins can accurately predict the water consumption trend of the water supply system and optimize the scheduling instructions and operation scheme through dynamic information interaction and mapping of process constraints, intermittent operating conditions, rolling rhythm, measured data, etc. between physical space and virtual space. Experimental results reveal that the proposed method can lessen power usage by 13.60% and water consumption by 10.54% regarding the premise of ensuring what is needed of cooling procedures. In addition, the water pump can maintain high effectiveness during operation to guarantee the security and stability of laminar cooling water supply systems. Highlights: Scheduling based on digital twins solves issues of energy abuse in complex systems. Prediction model based on OS-ELM keeps supply–demand balance of system scheduling. ISSA keeps the success rate of solving operation scheme during scheduling cycle. Performance of the traditional optimal scheduling gradually deteriorates over time. Iterative optimization by digital twin keeps scheduling performance of the system.